2020
DOI: 10.1186/s12862-020-01714-4
|View full text |Cite
|
Sign up to set email alerts
|

Globins in the marine annelid Platynereis dumerilii shed new light on hemoglobin evolution in bilaterians

Abstract: Background How vascular systems and their respiratory pigments evolved is still debated. While many animals present a vascular system, hemoglobin exists as a blood pigment only in a few groups (vertebrates, annelids, a few arthropod and mollusk species). Hemoglobins are formed of globin sub-units, belonging to multigene families, in various multimeric assemblages. It was so far unclear whether hemoglobin families from different bilaterian groups had a common origin. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 80 publications
(118 reference statements)
2
15
0
Order By: Relevance
“…Cluster 1 shows specific expression of the homeodomain transcription factors lhx6 and phox2 and an ap2 family member, while cluster 6 composed of dark neurosecretory cells shows specific expression of two neurosecretion markers, atrial natriuretic peptide receptor anpra and prohormone convertase phc2 , identifying these as brain parts of the circular and apical nervous system, respectively ( Vergara et al, 2021 ; Arendt, 2021 ). Cluster 8, another neural cluster, is enriched for the oxidative stress marker cytoglobin ( globin-like ; Song et al, 2020 ) and the bHLH transcription factor mitf . Subclustering revealed three subclusters, one of which represents rhabdomeric photoreceptors of the adult eye ( Figure 3B , subcluster 8.1) that specifically express mitf and globin-like .…”
Section: Resultsmentioning
confidence: 99%
“…Cluster 1 shows specific expression of the homeodomain transcription factors lhx6 and phox2 and an ap2 family member, while cluster 6 composed of dark neurosecretory cells shows specific expression of two neurosecretion markers, atrial natriuretic peptide receptor anpra and prohormone convertase phc2 , identifying these as brain parts of the circular and apical nervous system, respectively ( Vergara et al, 2021 ; Arendt, 2021 ). Cluster 8, another neural cluster, is enriched for the oxidative stress marker cytoglobin ( globin-like ; Song et al, 2020 ) and the bHLH transcription factor mitf . Subclustering revealed three subclusters, one of which represents rhabdomeric photoreceptors of the adult eye ( Figure 3B , subcluster 8.1) that specifically express mitf and globin-like .…”
Section: Resultsmentioning
confidence: 99%
“…Cluster 1 shows specific expression of the homeodomain transcription factors lhx6 and phox2 and an ap2 family member, while cluster 6 composed of dark neurosecretory cells shows specific expression of two neurosecretion markers, atrial natriuretic peptide receptor anpra and prohormone convertase phc2 , identifying these as brain parts of the circular and apical nervous system, respectively ( Vergara et al (2021) ; Arendt (2021) ). Cluster 8, another neural cluster, is enriched for the oxidative stress marker cytoglobin ( globin-like ) ( Song et al (2020) ) and the bHLH transcription factor mitf . Subclustering revealed 3 subclusters, one of which represents rhabdomeric photoreceptors of the adult eye (Figure 4B, subcluster 8.1) that specifically express mitf and globin-like .…”
Section: Resultsmentioning
confidence: 99%
“…(2021); Arendt (2021)). Cluster 8, another neural cluster, is enriched for the oxidative stress marker cytoglobin (globin-like)(Song et al (2020)) and the bHLH transcription factor mitf. Subclustering revealed 3 subclusters, one of which represents rhabdomeric photoreceptors of the adult eye (Figure4B, subcluster 8.1) that specifically express mitf and globin-like.…”
mentioning
confidence: 99%
“…Because these analyses included highly contiguous cyclostome genomes plus newly released genomes from cartilaginous fish as well as representatives of the deepest-branching lineages of ray-finned fishes ( Du et al 2020 ; Bi et al 2021 ), we were able to resolve longstanding questions regarding the early stages of evolution of GbX genes in vertebrates. Since the time of its initial discovery ( Roesner et al 2005 ), GbX went from being an obscure gene found in a very limited sample of vertebrates to becoming a credible candidate to provide clues about the functional role of the ancestor of all animal globins ( Blank et al 2011 ; Song et al 2020 ). This paradigm change came with an increased interest in deciphering its evolutionary history and its still elusive functional role ( Burmester and Hankeln 2014 ; Keppner et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%